1996
DOI: 10.1177/030802269605900902
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy in the Reformed NHS: The Views of Therapists and Therapy Managers

Abstract: This article describes an exploratory study which considered the effect of the recent reforms of the National Health Service on the professional position of occupational therapists working within NHS trusts. The term ‘reforms’ refers to the overall Impact of Government legislation following the Influential Griffiths report of 1983, up to and including the NHS and Community Care Act 1990. In the absence of any other published empirical data on this subject, an exploratory study was carried out. Sixteen in-dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…These databases were sourced through the Clinical Information Access Program. Over the past 30 years, consistently high levels of job satisfaction have been found in occupational therapy (Bordieri, 1988; Davis & Bordieri, 1988; Hummell & Koelmeyer, 1999; Lysack, Stadnyk, Paterson, McLeod & Krefting, 1995; Nordholm & Westbrook, 1981; Pringle, 1996; Rees & Smith, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These databases were sourced through the Clinical Information Access Program. Over the past 30 years, consistently high levels of job satisfaction have been found in occupational therapy (Bordieri, 1988; Davis & Bordieri, 1988; Hummell & Koelmeyer, 1999; Lysack, Stadnyk, Paterson, McLeod & Krefting, 1995; Nordholm & Westbrook, 1981; Pringle, 1996; Rees & Smith, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, the focus and meaning of a participative philosophy may become diluted, prompting a review of its credibility as an effective management style. This would help to make sense of the emerging difference in values between managers and practitioners, as demonstrated by studies such as that by Pringle (1996).…”
Section: The Innovator and Broker Rolementioning
confidence: 99%
“…It may also require occupational therapy leaders to become involved in joint planning at a strategic level if the interests of the profession are to be acknowledged. Consequently, senior occupational therapists need to have a broader understanding of the changing pattern of services and the context in which they are delivered if they are to lead the whole profession into the next century (Pringle 1996).…”
Section: The New Nhs: Modern Dependablementioning
confidence: 99%
“…Much of the work that would traditionally have been c,mied out by occupational therapists is now being undertaken by others, such as nurses or health and social care assistants, or is no longer taking place (Pringle 1996). Lloyd Smith (1994) has identified that occupational therapists have struggli3d to define and articulate their roles and, if boundaries continue to be challenged, the profession needs to ensure that the unique contribution of occupational therapy to health and social services is not lost.…”
Section: New Role Developmentmentioning
confidence: 99%